1999
DOI: 10.1017/s0022215100144792
|View full text |Cite
|
Sign up to set email alerts
|

Chemical labyrinthectomy and cochlear implantation for Menière's disease – An effective treatment or a last resort?

Abstract: The surgical management of Menière's disease presents a difficult and controversial problem and includes various procedures ranging from ‘placebo operations’ to vestibular nerve section. The situation is even more complex in the case where the only hearing ear is affected. We present a case of severe debilitating vertigo due to Menière's disease that was treated by chemical labyrinthectomy and cochlear implantation. This unique management strategy allowed restoration of useful hearing and relief of vertigo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Case reports have demonstrated successful hearing rehabilitation with CI after surgical labyrinthectomy, 23,24 and similar results have been reported after intratympanic gentamycin therapy. 5 Our cohort included 2 (patients 2 and 6) who underwent such procedures in the contralateral ear. Nevertheless, labyrinthectomy, either surgical or pharmacologic, should not be a contraindication to CI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports have demonstrated successful hearing rehabilitation with CI after surgical labyrinthectomy, 23,24 and similar results have been reported after intratympanic gentamycin therapy. 5 Our cohort included 2 (patients 2 and 6) who underwent such procedures in the contralateral ear. Nevertheless, labyrinthectomy, either surgical or pharmacologic, should not be a contraindication to CI.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the available literature revealed that only a handful of English-language articles investigating CI in the setting of MD have been published. [4][5][6][7][8] Most of these are single case reports and opinion articles and focus primarily on the effects of CI on hearing performance in patients with MD. Only 1 study has addressed the effects of CI on the nonhearing aspects of MD.…”
mentioning
confidence: 99%
“…10,11 Only the cochlear neurons are required for electrical stimulation, but with very high ablative doses of gentamicin, the risk of damage and reduced efficacy of cochlear implantation remains a possibility. In 1997, Wareing and O'Connor 9 published a review of the literature and suggested that this would be a viable treatment option and that this method of labyrinthectomy may be preferable in causing less trauma to the cochlea than transcanal labyrinthectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In MD, labyrinthectomy was first performed in 1895 as a destructive but very effective option for patients with treatment-resistant vertigo [9]. Recently this treatment has become more interesting again as hearing can be restored with a cochlear implant in a simultaneous procedure [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%